Context and Meaning: Roman Catholic Devotion to the Blessed Sacrament in Mid-Nineteenth-Century America - Taves, Ann (Church history, 1985)
A French visitor to a nineteenth-century Irish Catholic parish in the United States described the scene as follows: Behold them, when the sanctuary bell announces the moment of consecration; they raise their hands, they extend their arms in the form of a cross, they pray and sigh aloud; at times some leave their pew and prostrate themselves in the aisle, in order to assume a more suppliant and adoring attitude. … If you wait until the end of mass, you will be further edified. You will see them approach as near as possible to the high altar, before which they bow profoundly, making several genuflections, and frequently remain for a moment almost prostrate to the ground. From here they go to kneel at the altar of the Blessed Virgin, then before that of St. Joseph. Then follows a last and touching station before the body of the dead Christ which the Italians call the pietá; they pray here for a few moments, and respectfully press their lips to the five wounds of the Saviour. At the door of the church they take holy water, sign themselves with it repeatedly, and sprinkle their faces with it; then turning to the tabernacle they make a last genuflection, as if to bid farewell to our Lord, and finally withdraw.